Peningkatan Keterampilan Berbicara dengan Metode Debat Plus pada Pembelajaran Bahasa Inggris - Ahmad Hasanudin (Pusat Riset dan Inovasi Nasional, 2021)
Speaking skill is a language skill that needs to be mastered well in learning English. However, high school students still have difficulty conveying ideas, thoughts, questions and so on in English by using a variety of spoken language properly and correctly. The purpose of this research is to improve speaking skills in learning English using the Debate Plus method. The research method used is a class action research method in two cycles. The subjects of this study were students of class XI IPA SMA Negeri 3 Kota Tangerang Selatan with a total of 19 students consisting of 13 male students and 6 female students. Acquisition of student scores in pre-cycle was 43%, in cycle I was 64%, and in cycle II was 78%. The increase in the value of this test covers all aspects that are used as criteria, including aspects of understanding the problem, fluency in pronunciation, fluency in speaking, accuracy of sentence structure, accuracy of intonation, and accuracy of expression in speaking.